2012
DOI: 10.1001/archneurol.2012.1117
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Glucose Control, and 9-Year Cognitive Decline Among Older Adults Without Dementia

Abstract: To determine if prevalent and incident diabetes mellitus (DM) increase risk of cognitive decline and if, among elderly adults with DM, poor glucose control is related to worse cognitive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
195
2
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 270 publications
(220 citation statements)
references
References 32 publications
12
195
2
11
Order By: Relevance
“…They also develop cognitive decline more rapidly and at an earlier age (2). Identifying markers for very early cognitive decline in people with DM before the onset of evident impairment is therefore of interest and importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also develop cognitive decline more rapidly and at an earlier age (2). Identifying markers for very early cognitive decline in people with DM before the onset of evident impairment is therefore of interest and importance.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we examine the association between albuminuria status with performance on three tests of cognitive function in a cohort of adults with DM whose baseline eGFR level was approximately 90 ml/min per 1.73 m 2 . We further test whether decline in eGFR during follow-up was an independent risk factor for cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed no differences in cognitive measures in diabetic and nondiabetic controls, however, diabetic statin users had worse performance on tests of executive function, suggesting potentially worse vascular disease that could impact executive function [34]. Previous reports on neuropsychological testing in DM versus non-DM have varied from comparisons of a single test [35,36] to a comprehensive battery [37][38][39]. Generally, population-based studies tend to use briefer tests, while hospital-based research utilizes a more detailed battery.…”
Section: Discussionmentioning
confidence: 99%
“…1 The DCCT/EDIC study found that glycaemic control was associated with declining cognitive function and the ACCORD-MIND trial noted that, for each 1% rise in Hba1c, there was a 0.14 point drop in MMSE score. 2,3 In addition, studies have noted the effects of hypoglycaemia on increasing risk of cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%